Hungarian Monitoring, 8 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Unofficial list of Polish government composition - USSR: perestroika and press criticism - East German refugees Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) international press conference - Deputy ministerial talks on the future of Gabčíkovo-Nagymaros dam - Czech writer V. Havel's letter to Imre Pozsgay and Polish head of government Mazowiecki - National roundtable talks: role and future of TV - Election of Hungarian Socialist Workers' Party (MSZMP) congress delegates - Alliance of Free Democrats (SZDSZ) starts its election campaign Külpolitika: - Nem hivatalos lista a lengyel kormányról - SZU: peresztrojka és sajtókritika - Kelet - Német menekültügy Belpolitika: - MSZMP nemzetközi sajtókonferencia - Miniszterhelyettesi tárgyalások a bős-nagymarosi vízlépcsőrendszer jövőjéről - V. Havel cseh író levele Pozsgay Imréhez és Mazowiecki lengyel kormányfőhöz - A nemzeti kerekasztal-tárgyalások: a TV szerepe és jövője - MSZMP kongresszusi küldöttek választása - Az SZDSZ elkezdte a választási kampányt